AB0269 Joint Involvement and Pattern of Deformity and Its Relationship with Seropositivity in Rheumatoid Arthritis. (10th June 2014) - Rahman, M.M.; Samsuzzaman, S.M.; Choudhury, S.M.
Abstract : Background: Rheumatoid arthritis (RA) is the most common form of inflammatory arthritis and affects approximately 0.5-1% of the global population. Early diagnosis and treatment have been advocated to prevent structural damage and eventual long term disability. Bangladesh is a densely populated developing country where majority of the patients, suffering from RA, are being treated by general practitioners, orthopedists and internists because the country has very small number of rheumatologists Objectives: This study was conducted to see the joint involvement and the pattern of deformity and its relationship with seropositivity in patients with RA in Bangladesh. Methods: The study was carried out in the Department of Medicine, Sir Salimullah Medical College and Mitford Hospital, Dhaka over a period of 9 months from October 2010 to June 2011. A total of 100 RA patients, fulfilling the 1987 American College of Rheumatology (ACR) classification criteria, were the study population. Results: All patients had pain in bilateral metacarpophalengial joints. 93% patients had bilateral tarsal and metatarsophalengial joint pain. Bilateral wrist pain and ankle pain were present in 90% of cases. Over 40% complained of pain in both elbow joints while 65% had pain in both knee joints. Swelling of the joints was found in small joints of the hands (98%) and foot (86%), in wrist (85%) ankle (80%) and knee joints (65%) on both sides. Elbow joint swelling was not frequently seen (20%). Joint deformity was found in 63% of cases. Swan-neck deformity in index finger was present in 16% cases, in middle finger in 46% and in ring finger in 38.1% of cases. The boutonniere deformity of middle finger and the Z-deformity of thumb were detected in 7.9 and 4.8% respectively. The mean duration of swan neck, boutonniere and Z-deformity were 22.4±5.7, 15.6±5.8 and 6.0±2.1 months respectively. 9% patients exhibited claw deformity of foot where the mean duration was 3 months. 46% of the patients had deformity of both wrist joints. The mean durations of wrist and elbow deformities were 51.4±6.7 and 12.0±4.5 months respectively. Hand deformity was significantly higher in patients (79.2%) with positive anti-cyclic citrullinated peptide antibody (anti-CCP antibody) when compared to patients with negative anti-CCP antibody (p<0.001). Similarly, wrist joint deformity tend to have higher affinity for positive anti-CCP antibody (p=0.036). Deformities involving hand and wrist joints were more associated with positive RA tests (p<0.001 and p=0.048 respectively). Conclusions: RA patients with hand and wrist joint deformities have significantly higher tendency to be seropositive (anti-CCP antibody and RA positive). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4472